Risk, Transgression and Substance Use: An Ethnography of Young British Tourists in Ibiza - Briggs, Daniel; Turner, Tim (Studies of Transition States and Societies, 2011)
British youth have a notorious reputation for binge drinking, drug use, sex and risk behaviours within most major European holiday resorts. Consequently, there is much concern about their social activities abroad - especially in the Spanish Balearics. While research has documented these behaviours among British youth on these islands, it has tended to rely on survey data and oﬀ ered little understanding of why these behaviours might take place. This is the principle aim of our paper. Our research aims were to examine the drinking attitudes among British youth abroad and investigate the reasons that underpin these attitudes. Additional research interests were drug use, sex and risk behaviours. The paper is based on ﬁ ndings from ethnographic research with British youth in San Antonio, Ibiza. We spent one week with British youth and undertook participant observation and 17 focus groups (equating to 97 young people aged 17 to 31). The data suggests that British youth engage in these behaviours because they are exciting; to escape the constraints of work and family in the UK; and because these behaviours are integral to the construction of their life biographies and identities. The data also indicates that these behaviours are aggressively endorsed by various aspects of the social context of Ibiza.